2022
DOI: 10.1007/s12094-022-02976-8
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-576-5p promotes endometrial cancer cell growth and metastasis by targeting ZBTB4

Abstract: Purpose MicroRNAs (miRNAs) have already been shown to have a strong correlation with the invasion and metastasis capacity of tumor cells. The present research examined the function of miRNA-576-5p (miR-576-5p) in the development of endometrial cancer (EC). Methods miR-576-5p and ZBTB4 expression in EC and benign endometrial tissues was measured using quantitative real-time PCR (qRT-PCR) and western blot. To evaluate the proliferation ability of tumor cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
2
0
2
Order By: Relevance
“…В тканях аденокарциномы толстого кишечника была также выявлена усиленная экспрессия miR-576-5p, которая заметно способствовала пролиферации, миграции и инвазии клеток через регулятор роста нейронов 1 (NEGR1), который может являться основной терапевтической мишенью при аденокарциноме толстого кишечника [ 81 ]. Также повышенная экспрессия miR-576-5p была выявлена при раке эндометрия [ 82 ], где miR-576-5p способствовала пролиферации и метастазированию клеток рака эндометрия путем ингибирования экспрессии ZBTB4.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…В тканях аденокарциномы толстого кишечника была также выявлена усиленная экспрессия miR-576-5p, которая заметно способствовала пролиферации, миграции и инвазии клеток через регулятор роста нейронов 1 (NEGR1), который может являться основной терапевтической мишенью при аденокарциноме толстого кишечника [ 81 ]. Также повышенная экспрессия miR-576-5p была выявлена при раке эндометрия [ 82 ], где miR-576-5p способствовала пролиферации и метастазированию клеток рака эндометрия путем ингибирования экспрессии ZBTB4.…”
Section: Discussionunclassified
“…Промотор канцерогенеза [80] Cr толстого кишечника (↑) [81] Cr эндометрия (↑) [82] Примечание: Cr -карцинома; ПЖ -поджелудочная железа; МЖ -молочная железа; ГЦК -гепатоцеллюлярная карцинома; ПРЩЖ -папиллярный рак щитовидной железы; (↓) -сниженная экспрессия; (↑) -повышенная экспрессия.…”
Section: Discussionunclassified
“…3’UTR luciferase reporter assays were conducted as described previously [ 14 ]. Briefly, the 3’UTR of CYBB, including the wild-type (WT) or mutant-type (Mut) binding sites, was cloned downstream of the Renilla psiCHECK2 vector.…”
Section: Methodsmentioning
confidence: 99%
“…Increasing the expression of ZBTB4 inhibited the process of cell proliferation, colony formation and metastasis, while reducing the expression induced cell proliferation, colony formation and metastasis. Thus, it was concluded that miR-576-5p may regulate the development of tumor cells in endometrial cancer by targeting ZBTB4 [ 88 ].…”
Section: Role Of Mirnas In Uterine Cancermentioning
confidence: 99%